Pooled Patient-Level Analysis of Inclisiran Trials in Patients With Familial Hypercholesterolemia or Atherosclerosis - Wright, R Scott; Ray, Kausik K; Raal, Frederick J; Kallend, David G; Jaros, Mark; Koenig, Wolfgang; Leiter, Lawrence A; Landmesser, Ulf; Schwartz, Gregory G; Friedman, Andrew; Wijngaard, Peter L J; Garcia Conde, Lorena; et al. (Journal of the American College of Cardiology, 2021)
Inclisiran is a double-stranded small interfering RNA that suppresses proprotein convertase subtilisin-kexin type 9 (PCSK9) translation in the liver, leading to sustained reductions in low-density lipoprotein cholesterol (LDL-C) and other atherogenic lipoproteins with twice-yearly dosing. The purpose of this study was to conduct a patient-level pooled analysis from 3 phase 3 studies of inclisiran. Participants with heterozygous familial hypercholesterolemia (ORION-9 [Trial to Evaluate the Effect of Inclisiran Treatment on Low Density Lipoprotein Cholesterol (LDL-C) in Subjects With Heterozygous Familial Hypercholesterolemia (HeFH)]), atherosclerotic cardiovascular disease (ASCVD) (ORION-10 [Inclisiran for Participants With Atherosclerotic Cardiovascular Disease and Elevated Low-density Lipoprotein Cholesterol]), or ASCVD and ASCVD risk equivalents (ORION-11 [Inclisiran for Subjects With ASCVD or ASCVD-Risk Equivalents and Elevated Low-density Lipoprotein Cholesterol]) taking maximally tolerated statin therapy, with or without other LDL-C-lowering agents, were randomly assigned in a 1:1 ratio to receive either inclisiran or placebo, administered by subcutaneous injection on day 1, day 90, and every 6 months thereafter for 540 days. The coprimary endpoints were the placebo-corrected percentage change in LDL-C level from baseline to day 510 and the time-adjusted percentage change in LDL-C level from baseline after day 90 to day 540. Levels of other atherogenic lipoproteins and treatment-emergent adverse events were also assessed. A total of 3,660 participants (n = 482, n = 1,561, and n = 1,617 from ORION-9, -10, and -11, respectively) underwent randomization. The placebo-corrected change in LDL-C with inclisiran at day 510 was -50.7% (95% confidence interval: -52.9% to -48.4%; p < 0.0001). The corresponding time-adjusted change in LDL-C was -50.5% (95% confidence interval: -52.1% to -48.9%; p < 0.0001). Safety was similar in both groups. Treatment-emergent adverse events at the injection site were more frequent with inclisiran than placebo (5.0% vs. 0.7%), but were predominantly mild, and none were severe or persistent. Liver and kidney function tests, creatine kinase values, and platelet counts did not differ between groups. These pooled safety and efficacy data show that inclisiran, given twice yearly in addition to maximally tolerated statin therapy with or without other LDL-C lowering agents, is an effective, safe, and well-tolerated treatment to lower LDL-C in adults with heterozygous familial hypercholesterolemia, ASCVD, or ASCVD risk equivalents.